Model Pembelajaran Collaborative Problem Solving Untuk Meningkatkan Kemampuan Representasi Matematis - BARKAH SETIAWAN ADI (Departemen Matematika, 2019)
The purpose of this study is to find out whether students’ mathematics representation skill who studied with collaborative problem solving models better then students’ mathematics representation skill who studied with conventional models. This study was a quasi-experiment with Nonequivalent posttest-only control group design, and sampling was done by using Simple Random Sampling which consist of experiment class that will studied with collaborative problem solving models and control class that will studied with conventional models. The result of this study show that mean of students’test outcome in experiment class more than mean of students’test outcome in control class significantly. Thus, students’ mathematics representation skill who learn with collaborative problem solving models better then students’ mathematics representation skill who learn with conventional models. Keywords — Collaborative Problem Solving, Mathematics Representation, Simple Random Sampling, Nonequivalent posttest-only control group design.